Increases in subsistence farming due to land reform have negligible impact on bird communities in Zimbabwe - Stephen Pringle; Ngoni Chiweshe; Martin Dallimer (Ecology and Evolution, 2022)
Abstract Habitat alterations resulting from land‐use change are major drivers of global biodiversity losses. In Africa, these threats are especially severe. For instance, demand to convert land into agricultural uses is leading to increasing areas of drylands in southern and central Africa being transformed for agriculture. In Zimbabwe, a land reform programme provided an opportunity to study the biodiversity response to abrupt habitat modification in part of a 91,000 ha dryland area of semi‐natural savannah used since 1930 for low‐level cattle ranching. Small‐scale subsistence farms were created during 2001–2002 in 65,000 ha of this area, with ranching continuing in the remaining unchanged area. We measured the compositions of bird communities in farmed and ranched land over 8 years, commencing one decade after subsistence farms were established. Over the study period, repeated counts were made along the same 45 transects to assess species' population changes that may have resulted from trait‐filtering responses to habitat disturbance. In 2012, avian species' richness was substantially higher (+8.8%) in the farmland bird community than in the unmodified ranched area. Temporal trends over the study period showed increased species' richness in the ranched area (+12.3%) and farmland (+6.8%). There were increased abundances in birds of most sizes, and in all feeding guilds. New species did not add new functional traits, and no species with distinctive traits were lost in either area. As a result, species' diversity reduced, and functional redundancy increased by 6.8% in ranched land. By 2020, two decades after part of the ranched savannah was converted into farmland, the compositions of the two bird communities had both changed and became more similar. The broadly benign impact on birds of land conversion into subsistence farms is attributed to the relatively low level of agricultural activity in the farmland and the large regional pool of nonspecialist bird species.